2022
DOI: 10.11591/ijere.v11i3.22337
|View full text |Cite
|
Sign up to set email alerts
|

Students’ satisfaction on learning calculus using open and distance learning method during COVID-19 pandemic

Abstract: In early 2020, due to the COVID-19 outbreak in Malaysia, all higher education institutions had to switch from face-to-face learning to open and distance learning (ODL) method. The main purpose was to prevent any further spread of the COVID-19 virus. This study aimed to identify factors carrying impacts on students’ satisfaction in learning calculus using ODL method. The sample consists of 224 students of Universiti Teknologi MARA (UiTM) Perak Branch, Tapah Campus who took calculus subjects using ODL method dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In Figure 2 states the number of respondents used is at least 252 respondents from the number of active students as many as 3,342 with. These results already represent the number of samples used in this research and it has been accomplished by Ahmad et al [36].…”
Section: Methodssupporting
confidence: 71%
“…In Figure 2 states the number of respondents used is at least 252 respondents from the number of active students as many as 3,342 with. These results already represent the number of samples used in this research and it has been accomplished by Ahmad et al [36].…”
Section: Methodssupporting
confidence: 71%
“…On the other hand, it also concluded that internet connection quality was among the factors that caused challenges in distance learning, which is consistent with the findings of our study [ 7 ]. Moreover, another study found that student-teacher interaction, teacher performance, course evaluation, design, and technique were factors influencing student satisfaction [ 11 ]. In our study, students showed satisfaction regarding the interactions, instructors, course design, and technology.…”
Section: Discussionmentioning
confidence: 99%
“…Innovation is the existence of advanced quality education. So that, teaching and learning activities are expected to lead to a technology base in each educational unit (Ahmad, 2022;Othman, 2022;Sadikin, 2021;Yedithia dkk., 2022). Educational game-based learning media is a learning approach suitable for students because students prefer playing games to learning (Agbo, 2021;Gounaridou, 2021;Hsiao, 2021;Kara, 2021;Mulhem, 2021) Based on the data above, the development of educational game-based learning media is very important, especially in Madrasah Ibtidaiyah Jayapura City.…”
Section: Introductionmentioning
confidence: 99%